(untitled) (Revista INTEREDU11, 2022)
This study aims to analyze the research trajectory of the competitive funds from the National Council of Education (CNED for its acronym in Spanish) and Funds for Research and Development in Education (FONIDE for its acronym in Spanish) assigned during the last decade, in Chile. A total of 156 projects awarded between 2009 and 2018 were selected, which were quantitatively analyzed according to analysis descriptors, such as lines of research, topics addressed, methodology, affiliation of the researchers, and the modality in the formation of the research team. The results indicate that the interests in Chile during such period were more concentrated in the lines of higher education, curriculum, pedagogy, and professional teaching practices, while topics related to processes of consolidation of a community of researchers, and on the need for a greater link between pedagogy and public policies did not present the same level of interest.